CUSTOMER VALUE PERCEPTION OF ISLAMIC BANKING IN INDONESIA - Surachman Surjaatmadja; Aini Kusniawati (Sosiohumaniora, 2023)
This study aims to find out, the factors that influence the perception of the customer value of Islamic Banks or IB in Indonesia. These factors are product knowledge by staff, service quality, and marketing communications. Customer value is one of the indicators of a company’s performance. The results show that the customer value of IB in Indonesia is perceived by its customers well by their understanding of IB products by staff, improving service quality and marketing communication. Service quality contributes greater than product knowledge by staff while marketing communication less than both. The method used in this study is descriptive which aims to obtain an overview of variable characteristics. Carried out through data collection, involving 200 respondents. The research methods used a descriptive survey and descriptive development. The type of investigation of this research is the analysis of quality. In this study analyzes the influence of independent variables on the dependent variable. The unit of analysis of this research is individuals, in this case, the prospective customers and customers of IB in Indonesia. The time period of data collection this research is a cross-section. Data collection is conducted from June to August 2018, where the data is processed using the SEM-PLS approach. The research results show that product knowledge, service quality and marketing communications have a positive and significant impact on customer value perceptions. Service quality has a more dominant influence on customer value perceptions than product knowledge and marketing communications.